On 3-share threshold implementations for 4-Bit S-boxes - Kutzner, Sebastian (2013)
One of the most promising lightweight hardware countermeasures against SCA attacks is the so-called Threshold Implementation (TI) [12] countermeasure. In this work we discuss issues towards its applicability and introduce solutions to boost its implementation efficiency. In particular, our contribution is three-fold: first we introduce two methodologies to efficiently implement 3-share TI to a given S-box. Second, as an example, we successfully apply these methodologies to PRESENT and are able to decrease the area requirements of its protected S-box by 37-40%. Third, we present the first successful practical Mutual Information Attack on the original 3-share TI implementation of PRESENT and compare it with a correlation-enhanced collision attack using second-order moments.